The Basic Analysis of the Morpho-Syntactic Status of the Third Person Singular Subject Pronoun in Standard Yorùbá Language. - Adekunle, Moses Adedire (NIU Journal of Humanities, 2023)
Awóbùlúyì (2001) brings a new notion of the zero morphological realization of the first person singular pronoun (ó) in Yorùbá studies. Awóbùlúyì’s (2001:1-8) proposition hereby trigger arguments on the ‘ó’ as the first person singular pronoun subject with different views and submissions from scholars. (see Àkànbí 2004, O̩ládèyí 2003 and Adéwo̩lé 2011). Awóbùlúyì (2001:2) hints that his preposition emerged because ‘ó’ and ‘un’ are not linguistically related. Using clipping and descriptive analysis, this paper has tried to claim that ‘ò’, ‘ó’ ‘ún’, are reductions of ‘òun’ (pronominal) in Yorùbá language. The paper supported Awóbùlúyì (1992) previous position that pronouns are reduction form of pronominals in the language. The study informed that adoption of variants of clipping formative styles such as fore clipping or apocopation clipping cause the different representation of the third person pronouns in Yorùbá  syntax from the following; ‘ó’, ‘ò’, ‘un’. The paper used examples from Ifè̩. Òǹdó and Kétu dialects. Our findings reveal that prosodic assimilation between the third person pronoun or pronominal with the high tone syllable eventually cause ‘o’ ‘ùn’ àwo̩n and wo̩n to transform to ó, ún, wó̩n and àwó̩n as deem fit in each phonetic realization of the third person pronouns and pronominals. The study hereby recommends that the agelong established presentation as of ‘ó’ as the third person singular pronoun should be retained. Therefore, the zero morphological theory is hereby discouraged. Keywords: Fore-clipping, apocopation clipping, Anglo-phone Kétu, pscho-morphological, morphological restrictions.